PTU-132 Hepatology E-consultation: The Way Forward? A Review Of Our Initial Experience And Cost Analysis. (9th June 2014) - Moreea, S; Southern, PB; Connolly, J; Appleby, VJ
Abstract : Introduction: Outpatient visits to secondary care are costly to Primary Care (PC), time consuming for patients and not always appropriate. Our Trust having been a pioneer in nephrology e-Consultation (eC), we started a hepatology eC service in March 2012. This allows patients' records to be shared between PC and secondary care (SC) without the need for a detailed referral letter. Our aims were to analyse our initial experience and perform a cost analysis of hepatology eC. Methods: Retrospective analysis of eC between Mar 12- Oct 13 using SystmOne. Tariffs used for cost analysis: new patient (NP) referral £181, follow up (FU) £103, eC £24. Results: In 18 months there were 81 eC (31M/50F mean age 52/56 y), each taking 10–15 min to complete. The median response time was 2 days (43% within 1 day). Referral reasons: isolated raised bilirubin/ALT/ALP/GGT: 44/81 (54%), mixed raised LFT's: 16/81 (20%), abnormal radiology 10%, hyperferritinaemia 9%, HBV/HCV 4%, general advice 2%. There was one inappropriate referral. In 18 cases, SC referral was recommended (22%), with 10/18 being referred and seen. The mean number of FU appointments was 3. Total cost to PC was £8, 114: eC £1, 944 and £6, 170 for subsequent referrals. A minimum cost saving of £14, 890 was made (81 NP (£14, 661) and assuming one FU for each (£8, 343)). Conclusion: eC is a rapid, cost-effective method of providing hepatology advice. Hidden costs including consultant time, clinic costs etc are difficult to quantify. We would, however, recommend eC as the way forward with a more appropriate tariff. Disclosure of Interest: None Declared.